What makes poor countries poor? : institutional determinants of development - Trebilcock, M. J. (Edward Elgar, 2011)
This book focuses on the idea that institutions matter for development, asking what lessons we have learned from past reform efforts, and what role lawyers can play in this field. It provides a critical overview of different conceptions and theories of development, situating institutional theories within the larger academic debate on development. The book also discusses why, whether, and how institutions matter in different fields of development. In the domestic sphere, the authors answer these questions by analyzing institutional reforms in the public (rule of law, political regimes and bureaucracy) and the private sectors (contracts, property rights, and privatization). In the international sphere, they discuss the importance of institutions for trade, foreign direct investment, and foreign aid.